Kualitas Fasilitas Difabel Kursi Roda Berdasarkan Pengguna Di Taman Kambang Iwak Besak, Palembang - Kurniatillah Rafida; Nurini Nurini (Teknik PWK (Perencanaan Wilayah Kota), 2021)
A good urban park should be easily accessible and friendly for people with disabilities because they have the same right in accessing the park. Kambang Iwak Besak Park is the most visited active urban park in Palembang. Besides, Kambang Iwak Besak Park is often visited by wheelchair disabilities people because there are some facilities that are available for them. However, there are some disabilities facilities problems, such as very steep ramps and the size of facilities for the wheelchair disabilities which do not met the standarFds yet. According to this quality problem of the wheelchair disabled facilities, this study aimed to find out the quality of the wheelchair facilities based on the users in Kambang Iwak Besak Park. This research used quantitative approach with descriptive analysis methods. Descriptive analysis was used to see the availability of the facilities wheelchair. The results of this study showed that the quality of wheelchair disabled facilities are still poor. From 6 variables, only 1 variable has good quality, which is the pedestrian path. The 5 variables that are still not good enough are the entrance lane, the parking area, the drinking place, and toilets. It is related to the accessibility of facilities, ease of access, comforts, and safety.